SMASH ΔΣ modulator with adderless feed‐forward loop filter. Issue 8 (1st April 2017) - Honarparvar, M.; de la Rosa, J.M.; Nabki, F.; Sawan, M.
Abstract : A novel cascade ΔΣ modulator, which combines the benefits of sturdy MASH (SMASH) topology and feed‐forward loop filter, is presented. The proposed ΔΣ architecture is based on moving the power‐hungry adder block from the quantiser input to the first integrator output. The proposed architecture shows a better operational transconductance amplifier (OTA) linearity and relaxed OTA DC‐gain compared with conventional MASH and SMASH topologies. This feature makes the modulator topology more suitable than conventional MASH and SMASH topologies for low‐voltage applications.